2020
DOI: 10.1177/0956247820965156
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing the COVID-19 pandemic’s impact on food security in two small cities in Bangladesh

Abstract: The COVID-19 pandemic is an evolving urban crisis. This research paper assesses impacts of the lockdown on food security and associated coping mechanisms in two small cities in Bangladesh (Mongla and Noapara) during March to May 2020. Due to restrictions during the prolonged lockdown, residents (in particular low-income groups) had limited access to livelihood opportunities and experienced significant or complete loss of income. This affected both the quantity and quality of food consumed. Coping strategies re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 16 publications
4
42
0
1
Order By: Relevance
“…Although their area coverage was broader than urban areas, they raised the importance of local food production for food security, especially for poor people, and the need for a transition towards sustainable food systems. This importance of local production was further conveyed by Ruszczyk, et al [12], who contextualized the COVID-19 pandemic's impacts on food security in two small cities in Bangladesh. They found that smaller cities have greater opportunities for practicing urban agriculture and they were, therefore, more able to improve the food security of city dwellers than bigger cities.…”
Section: Introductionmentioning
confidence: 98%
“…Although their area coverage was broader than urban areas, they raised the importance of local food production for food security, especially for poor people, and the need for a transition towards sustainable food systems. This importance of local production was further conveyed by Ruszczyk, et al [12], who contextualized the COVID-19 pandemic's impacts on food security in two small cities in Bangladesh. They found that smaller cities have greater opportunities for practicing urban agriculture and they were, therefore, more able to improve the food security of city dwellers than bigger cities.…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that these economic problems in households are associated with insufficient food intake, both in terms of amount and quality. However, families with persistent income or enough savings were seen to be less affected during the quarantine period (Ruszczyk et al, 2020). Food insecurity also makes people physically (Kelly et al, 2018) and mentally (Slavich, 2020) more vulnerable.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we report on the results of 14 indepth interviews with community members experiencing overlapping crises within a broader context of food insecurity. The study's contextualized postpositivist framing and use of in-depth interviews with community residents experiencing multiple crises (including COVID-19) were apropriatley positioned within the food insecurity literature (Beveridge et al, 2019;Ruszczyk et al, 2020). As such, this study sought to understand the experience of food insecurity in a way that was sensitive to participants' unique geographies and perspectives.…”
Section: Limitations and Future Researchmentioning
confidence: 99%